2021
DOI: 10.1177/00936502211042516
|View full text |Cite
|
Sign up to set email alerts
|

“Be Nice or Leave Me Alone”: An Intergroup Perspective on Affective Polarization in Online Political Discussions

Abstract: Affective polarization—growing animosity and hostility between political rivals—has become increasingly characteristic of Western politics. While this phenomenon is well-documented through surveys, few studies investigate whether and how it manifests in the digital context, and what mechanisms underpin it. Drawing on social identity and intergroup theories, this study employs computational methods to explore to what extent political discussions on Reddit’s r/politics are affectively polarized, and what communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 104 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…We found that this mechanism had a positive effect in encouraging more deliberate participation across users. The effect of diversity on reducing affective polarization has gained scholarly attention [1,3,17,23,30,37,42]. While aggregated UGLs improved participants' understanding of others' multifaceted evaluation of a comment, our findings show that simply increasing exposure to diversity does not increase the tolerance towards the outgroup.…”
Section: The Effect Of Showing Diverse Reactionsmentioning
confidence: 59%
“…We found that this mechanism had a positive effect in encouraging more deliberate participation across users. The effect of diversity on reducing affective polarization has gained scholarly attention [1,3,17,23,30,37,42]. While aggregated UGLs improved participants' understanding of others' multifaceted evaluation of a comment, our findings show that simply increasing exposure to diversity does not increase the tolerance towards the outgroup.…”
Section: The Effect Of Showing Diverse Reactionsmentioning
confidence: 59%
“…The present analysis contributes to the literature on the roots of affective polarization. Marchal (2022) concluded that conversations (with negative critique) and group context spur affective polarization. Lelkes (2021) reported that some scholars point to ideological values and elite messages as sources of affective polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Wojcieszak and Warner (2020, p. 792) suggest that in‐group contact may be more frequent than out‐party contact (for a similar proposition, see Marchal (2022, p. 7); both studies utilize American data). Our material does not fully confirm this claim; in particular, the superficial contact indicator is clearly skewed in favor of out‐party contact (see Figure online appendix).…”
mentioning
confidence: 99%
“…Missing from this literature is microlevel, qualitative investigation of how affective polarization takes shape in people's talk. The few qualitative studies have looked only at elite discourse (e.g., Meislová, 2022) or social media (e.g., Marchal, 2022; Pettersson & Sakki, 2023; Sakki & Martikainen, 2021). The present article's analysis of lay interviews promises to fill the gap.…”
Section: Affective Polarization and The Rise Of Right‐wing Populismmentioning
confidence: 99%